On the Polynomial Asymptotics of Subharmonic Functions of Finite Order and their Mass Distributions - Azarin, Vladimir (Журнал математичної фізики, аналізу, геометрії, 2007)
We obtain the results analogous of those of [5] on the polynomial asymptotics with arbitrary 0<ρ_n<…<ρ_1<ρ, defining multipolynomial terms. Mathematics Subject Classification: 30D20, 30D35, 31A05, 31A10.